The World as Database: On the Relation of Software Development, Query Methods, and Interpretative Independence. - Gugerli, David (Information & Culture, 2012)
The article explores the history of the development of database technologies by considering its relationship to software development, query methods, and user interpretation of data. An extended metaphor for the progress in database development is made by comparing the television crime shows "Columbo" and "CSI." A historiography of computers considers the writings of scholars Paul Edwards on computer users, software history by Martin Campbell-Kelly, and the social history of computers by Thomas Haigh.